Is Price Still King? Exploring What Really Drives Consumers to Choose Mobile Operator SIM Cards in Batam, Indonesia - Sri Yusriani (International Journal of Advanced Multidisciplinary, 2026)
This study explores the key factors influencing consumer decisions when purchasing mobile operator SIM cards in Batam, Indonesia. Using a qualitative descriptive approach, perceptions were gathered from diverse community segments, including students, homemakers, private-sector employees, and government staff. The findings indicate that price remains the most dominant determinant across groups, followed by promotional strategies. Customer experience, particularly network quality and service interaction, plays a supporting but less decisive role. The study suggests that telecom providers in emerging urban markets should prioritize competitive pricing structures, targeted promotions, and continuous service quality improvements to strengthen consumer acquisition and retention.